Effects of γ-radiation on chickpea (Cicer arietinum) varieties and their tolerance to salinity stress - Amal Abdel-Nasser ABDOUN; Laila MEKKI; Aladdin HAMWIEH; Abdelfattah BADR (Acta Agriculturae Slovenica)
Chickpea (Cicer arietinum L.) is a bisexual and self-pollinated legume. It improves the soil fertility through its natural ability to fix atmospheric nitrogen with its symbiotic bacteria. Salinity is one of the most important abiotic stress factors affecting plant growth. γ-radiation is a very effective tool for inducing mutations in many plants. This study evaluated the γ-radiation effect on germination, cell division and plant growth of first-generation plants. Seeds of seven chickpea varieties were irradiated with γ-radiation doses ranging between 50 Gy and 600 Gy. Non-significant differences in germination percentage were recorded for seeds exposed to 50 Gy, 100 Gy, and 200 Gy of γ-radiation in comparison to the corresponding controls except ILC 484. The mitotic index (MI) of root cells increased at the low doses of 50 Gy, 100 Gy and 200 Gy comparing and reduced at the higher doses in all chickpea varieties to the control. All doses of γ-radiation induced a variable range of chromosomal abnormalities; the most common were bridges, laggard chromosomes, stickiness at metaphase, chromosome breaks, micronuclei and binucleate cells. The 300 Gy to 600 Gy doses induced degradation of nuclear membranes. The salinity treatments at 25 mM NaCl and 60 mM NaCl reduced seedling’s growth of all cultivars. The dose of 100 Gy alleviated the impact of salinity at a concentration of 25 mM NaCl for all varieties, except FLIP 84-188 and FLIP 97-263. The 60 mM NaCl treatment significantly reduced early growth of all cultivars and its effect was not alleviated by the γ-radiation.